On Existence of Weakly Maximal Programmes in a Multi-Sector Economy - Brock, W. A. (Review of Economic Studies, 1970)
Journal Article On Existence of Weakly Maximal Programmes in a Multi-Sector Economy Get access W. A. Brock W. A. Brock University of California, Berkeley and University of Rochester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 2, April 1970, Pages 275–280, https://doi.org/10.2307/2296419 Published: 01 April 1970 Article history Received: 01 July 1968 Accepted: 01 June 1969 Published: 01 April 1970